Brownie R Us / Nur Azreena A Adam and Maizatul Shima Ramly - A Adam, Nur Azreena; Ramly, Maizatul Shima (2022)
Brownie r Us is a firm that sells art items to clients. Their brownie cakes are chewy and feature distinctive toppings, making them acceptable for people of all ages. Our primary goal as a firm is to provide brownie cakes with a superior flavor yet at an accessible price. Brownie r Us really offers premium and high-quality items to clients, ensuring that the completed products meet or exceed customer expectations. Furthermore, our items are reasonably priced, ranging from RM 15 to RM 20. Brownies have their own target market, which includes children, university students, and elders, because this cake may be cooked as an afternoon tea or offered to guests. Brownie cakes are among the most popular desserts nowadays, particularly among teens and university students who are more interested in viral and aesthetically pleasing items. In addition, Brownie r Us has numerous programmed to entice consumers, such as free delivery with a minimum purchase of two pax, a new year deal, and a Christmas offer. It strives for product consistency and consumer loyalty. Because we are an online business, the only online platforms we utilize are Facebook and WhatsApp, both of which the majority of people choose in the online world. According to observations, brownie cakes are surprisingly easy to attract internet shoppers because they are so popular nowadays. As a consequence of running this Brownie r Us business, we believe it has a lot of potential to grow if we continually encourage consumer input and demands.